2016
DOI: 10.4103/0970-0218.183590
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and factors associated with poor glycemic control among inpatients with diabetes mellitus type 2 as a primary diagnosis in a teaching hospital

Abstract: Context:Diabetes mellitus is a growing health problem in most countries. In Malaysia, there was an increase in prevalence over the years. This makes diabetes also a growing concern in Malaysia, which warrants strengthening of the prevention and control programme.Aims:This paper aims to describe the profiles of diabetes mellitus type 2 in tertiary setting and to identify the risk factors for high level of HbA1c among the study population. The findings will give a glimpse on current status of diabetes in our cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
4
8
1
2
Order By: Relevance
“…Other studies in Ethiopia indicated that 59.2-70.8% of patients did not achieve controlled blood glucose levels [ 4 6 ]. This phenomenon was also observed in other countries such as India (78.2% among patients with diabetes complications) [ 7 ], Malaysia (79.7%) [ 8 ], and Brazil (76%) [ 9 ]. Factors affecting glycaemic control in patients with DM are complex and varied [ 10 ], including socioeconomic (e.g., advancing age, male, or low education), clinical (e.g., long duration of treatment, adherence to regular follow-up, having comorbidities, or type of medications), or behavioral (e.g., lack of physical activity or smoking) characteristics [ 3 9 ].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other studies in Ethiopia indicated that 59.2-70.8% of patients did not achieve controlled blood glucose levels [ 4 6 ]. This phenomenon was also observed in other countries such as India (78.2% among patients with diabetes complications) [ 7 ], Malaysia (79.7%) [ 8 ], and Brazil (76%) [ 9 ]. Factors affecting glycaemic control in patients with DM are complex and varied [ 10 ], including socioeconomic (e.g., advancing age, male, or low education), clinical (e.g., long duration of treatment, adherence to regular follow-up, having comorbidities, or type of medications), or behavioral (e.g., lack of physical activity or smoking) characteristics [ 3 9 ].…”
Section: Introductionsupporting
confidence: 65%
“…The sample size was calculated by using the formula to estimate the proportion with specified absolute precision. With the confidence level = 95%, the expected proportion of uncontrolled glycaemic level = 79.7% (according to a previous study in Malaysia [ 8 ]), and the absolute precision = 0.06, the essential sample size was 173 patients. An addition of 15% of the total sample size was added to prevent people who did not accept to participate or not complete the interview, leading to a total of approximately 200 patients included in the sample frame.…”
Section: Methodsmentioning
confidence: 99%
“…Results in the present study may be owing to the fact that patients may well be physically active, hence their glucose utilisation remains high, which leads to normal blood glucose levels. In contrast, a similar Ethiopian study reported increasingly poor glycaemic control with age which became substantial above 58 years of age whereas Zambia reported high prevalence of poor glycaemic control in patients below 50 years of age [17,23]. Many factors such as lifestyles, concurrent illnesses and socioeconomic status could play a role [11,26].…”
Section: Discussionmentioning
confidence: 87%
“…The minimum sample size required for this study was 303. This sample size was calculated using the Dobson's formula at a confidence interval of 95%, maximum tolerable error of 5% and prevalence of 27% [17].…”
Section: Sample Sizementioning
confidence: 99%
“…Being unemployed or retired and having up to tertiary education are all protective factors against poor glycaemic control. Psychiatric disorders, such as depression and anxiety, have not been found to be predictive of glycaemic control in Malaysian diabetic patients [9][10][11]. However, personality traits, such as type D personality (social inhibition, negative affectivity, and neuroticism), have previously been associated with diabetes mellitus [12].…”
Section: Introductionmentioning
confidence: 99%